2008
DOI: 10.1021/om800097b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structural Characterization, and Ethylene Polymerization Behavior of the Vanadium(III) Complexes Bearing Salicylaldiminato Ligands

Abstract: Vanadium(III) complexes bearing salicylaldiminato ligands (2a-k) [RNdCH(ArO)]VCl 2 (THF) 2 (Ar ) C 6 H 4 , R ) Ph, 2a; p-CF 3 Ph, 2b; p-CH 3 Ph, 2c; 2,6-Me 2 Ph, 2d; 2,6-iPr 2 Ph, 2e; cyclohexyl, 2f; Ar ) C 6 H 3 tBu(2), R ) Ph, 2g; 2,6-iPr 2 Ph, 2h; Ar ) C 6 H 2 tBu 2 (2,4), R ) Ph, 2i; 2,6-iPr 2 Ph, 2j; Ar ) C 6 H 2 Br 2 , R ) Ph, 2k) were prepared from VCl 3 (THF) 3 by treating with 1.0 equiv of (RNdCH)ArOH in tetrahydrofuran (THF) in the presence of excess triethylamine (TEA). The reaction of VCl 3 (THF) 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
60
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 67 publications
(55 reference statements)
9
60
0
Order By: Relevance
“…of salicylaldiminato ligand in tetrahydrofuran (THF) afforded vanadium(III) complexes 4a-o in moderate to high yields (Fig. 6) [59]. X-ray crystallographic analysis showed that the geometry of the molecular structure was similar to those of mono(␤-enaminoketonato) vanadium(III) complexes (Fig.…”
Section: Mono(salicylaldiminato) Vanadium(iii) Complexesmentioning
confidence: 87%
See 1 more Smart Citation
“…of salicylaldiminato ligand in tetrahydrofuran (THF) afforded vanadium(III) complexes 4a-o in moderate to high yields (Fig. 6) [59]. X-ray crystallographic analysis showed that the geometry of the molecular structure was similar to those of mono(␤-enaminoketonato) vanadium(III) complexes (Fig.…”
Section: Mono(salicylaldiminato) Vanadium(iii) Complexesmentioning
confidence: 87%
“…of salicylaldimine ligands were added to VCl 3 (THF) 3 , bis(salicylaldiminato) vanadium(III) complexes were formed (Fig. 6) [59]. Molecular structures showed that the steric obstacles have a remarkable effect on the configuration of bis(salicylaldiminato) vanadium complexes.…”
Section: Bis(salicylaldiminato) Vanadium(iii) Complexesmentioning
confidence: 99%
“…The observed activities by certain complexes were slightly/apparently higher than those by VCl 3 (THF) 3 , and the activities decreased at 70 8C probably due to the rapid deactivation even for short period (5 min) and in the presence of excess amount of re-oxidant (300 equivalent to V). On the basis of these data, it seems that 26b (R [101][102][103][104]. Placement of neutral donor ligands (amine, pyridine) into the phenoxy-imine ligands in 27 was not effective; the observed activity by 27 h was relatively close to 26e.…”
Section: C 19dmentioning
confidence: 92%
“…A series of vanadium(III) complexes containing b-enaminoketonato [99, 100], phenoxy-imine [101][102][103][104], imino-pyrrolide [105] ligands (exemplified in Scheme 3.11) were tested as olefin polymerization catalyst in the presence of Et 2 AlCl and Cl 3 CCO 2 Et. The selected results are summarized in Table 3.5 [99,100,103,105].…”
Section: C 19dmentioning
confidence: 99%
“…[19] Research has shown that TiO 2 can improve the thermal stability of the polymer properties, since it has antioxidant and flame retardant characteristics. [26] The use of metallocene catalysts with titanium dioxide as a nanofiller is an excellent combination to improve polymer properties. [14] In this study, we used titanium dioxide doped with iron (TiO 2 /Fe) to investigate the effects of iron on the ethylene homopolymer and ethylene/propylene copolymer properties.…”
Section: Introductionmentioning
confidence: 99%